2015
DOI: 10.1111/ijd.12801
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD4+CD25highFoxP3+ T‐regulatory cells in patients with atopic dermatitis after narrowband‐ultraviolet B phototherapy

Abstract: Significant reduction in AD disease severity is correlated with the change in Tregs% and Tregs/Teffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…The results suggest that this does not apply to a group of patients with AD only. In contrast to our data, a recent study from Egypt (31) showed that numbers of circulating regulatory T cells were increased significantly after 6 weeks of nbUVB phototherapy in AD patients, but the authors did not assess FLG genotype. Comparisons with our study should be made with caution, because the study from Egypt was based on patients with more severe disease, different ethnicity, and different time points of follow-up.…”
Section: Neither the Phenotype Of The Cd4 + T Cells In The Blood Nor contrasting
confidence: 99%
“…The results suggest that this does not apply to a group of patients with AD only. In contrast to our data, a recent study from Egypt (31) showed that numbers of circulating regulatory T cells were increased significantly after 6 weeks of nbUVB phototherapy in AD patients, but the authors did not assess FLG genotype. Comparisons with our study should be made with caution, because the study from Egypt was based on patients with more severe disease, different ethnicity, and different time points of follow-up.…”
Section: Neither the Phenotype Of The Cd4 + T Cells In The Blood Nor contrasting
confidence: 99%
“…Ultraviolet (UV) radiation has been shown to be an effective treatment modality in moderate-to-severe AD due to its proposed ability to decrease Staphylococcus aureus colonization, improve skin barrier function, reduce pruritis, and decrease tissue inflammation associated with AD 46,47. Four hundred and twenty-eight studies and 19 RCTs that enrolled over 900 subjects found medium-dose UVA1 phototherapy and narrowband (NB)-UVB phototherapy to be the safest and most effective phototherapies for moderate-to-severe AD subjects, with similar efficacy 4851.…”
Section: Treatmentsmentioning
confidence: 99%
“…By reducing the number of epidermal nerve fibers and the expression of axon guidance molecules, it is also considered a good therapeutic approach for AD-associated itch, relieving patients from this oppressive symptom [26, 27]. Moreover, UV irradiation is also able to modulate the immune response of AD patients via upregulation of FoxP3-positive regulatory T cells, whose number is directly correlated with the degree of AD severity score improvements [28]. Different artificial light sources are available against AD: broadband UVB (290–320 nm), narrow-band (NB) UVB (311–313 nm), excimer laser (308 nm), UVA-1 (340–400 nm), psoralens and UVA (PUVA), and combined UVA/UVB (280–400 nm).…”
Section: Methodsmentioning
confidence: 99%